Libertarianism and Ayn Rand's philosophy of objectivism - M. I. Korobko (Ukrainian Cultural Studies, 2019)
The article gives an overview of the ideology of libertarianism. The purpose of the article is analyzing the main ideas of the libertarian movement and how they relate to the philosophy of Ayn Rand's objectivism. The essence of this ideological and political direction can not be imagined without the philosophical work of American writer Ayn Rand. The main idea of libertarians is to uphold market freedoms and to object to redistribution through taxation to implement the liberal theory of equality. This movement gets its modern meaning in the late 30's and early 40's of the twentieth century in the United States, when enough opponents of the New Deal policy of US President F. Roosevelt appeared. Ayn Rand was one of the first to support libertarians, but later she began to distance herself from them for a variety of reasons, both personal and philosophical. In Ukraine today, this movement has gained popularity due to the ideological direction of the political party "Servant of the People".Today, members of the libertarian political movement are engaged in promoting and spreading the ideas of "objectivism" among the masses in the United States. This movement, which took classical liberal theory as a basis, originated in the American tradition of individualism as a result of dissatisfaction with the transformation of the liberal idea in the practice of political liberalism toward socialism and developed into a sufficiently strong political flow.Ayn Rand's achievements do not lose their relevance in times of global crisis as a means of overcoming the state of despair. It inspires hope that man himself can achieve a happy life unlike most modern ethical theories that cannot refute a person's ultimate dependence as a small screw in the world mechanism. But the ideology of libertarianism, inspired by the American writer, though tempting uninformed people with their possible "independence" of society from the state machine, still remains a rather ambiguous political ideology.
Keywords: Ayn Rand, ideology, capitalism, libertarianism, objectivism, politics